2009
DOI: 10.1021/cm9025057
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Copolymers Containing Bithiophene and Dialkoxynaphthalene for the Applications to Field Effect Transistor and Photovoltaic Cell: Performance and Stability

Abstract: Poly(5′,5′′-bithiophene-alt-2,6-[(1,5-didecyloxy)naphthalene]) (PBDN) was synthesized from 2,6-dibromo-l,5-didecyloxynaphthalene and 1,1′-[2,2′-bithiophene]-5,5′-diylbis[1,1,1-trimethylstannane] and was used as the active layer in organic thin-film transistors (OTFTs) and organic photovoltaic cells (OPVs). The obtained PBDN was soluble in organic solvents such as chloroform, chlorobenzene, and toluene and had a weight-averaged molecular weight of 9100, with a polydispersity index of 1.31. The photoluminescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 58 publications
0
49
0
Order By: Relevance
“…Intriguingly, the copolymers exhibited low HOMO levels, which allow PSCs to have high V oc [63]. Compared with previous polymer systems composed of electron-rich triphenylamine and electron-deficient BT derivatives, such low HOMO levels of copolymers may be originated from the naphthalene unit introduced into the triarylamine [36,41,44,45].…”
Section: Electrochemical Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Intriguingly, the copolymers exhibited low HOMO levels, which allow PSCs to have high V oc [63]. Compared with previous polymer systems composed of electron-rich triphenylamine and electron-deficient BT derivatives, such low HOMO levels of copolymers may be originated from the naphthalene unit introduced into the triarylamine [36,41,44,45].…”
Section: Electrochemical Propertiesmentioning
confidence: 97%
“…1. Replacement of the phenyl rings of the triphenylamine with other aromatic rings such as naphthalene could be a quite efficient method to control the energy level of the copolymer, and Kwon group has reported incorporation of naphthyl groups lowers the HOMO energy level of the copolymers and increase V oc of the solar cell devices [35,44,45]. From this point of view, we introduced two (2-ethylhexyloxy)-naphthyl groups to the triarylamine moiety to render solubility of the copolymer and further control the HOMO energy level and V oc .…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, dialkoxylnaphthalene-based copolymers are seldom explored, and their photovoltaic performances are inferior to those of many D-A copolymers [21e24]. For example, the first alternating copolymer based on bithiophene and didecyloxynaphthalene was demonstrated to exhibit an open circuit voltage (V oc ) of 0.83 V and a power conversion efficiency (PCE) of 1.3% when blended with [6,6]-phenyl-C61-butyric acid methyl ester [21]. Later on, Kwon et al developed two alternating copolymers based on the didecyloxynaphthalene and 2,3-bis-(thiophene-2-yl)acrylronitrile.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] OTFTs based on solution-processable organic semiconductors have been increasingly investigated for use in low-cost memory devices, large-area display devices, and flexible electronic devices. [13][14][15][16] Especially, easy solution-processable polymeric semiconductors can be deposited using low-cost solution processing methods such as spin-coating, ink-jet printing, and gravure printing.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, because P3HT have relatively low ionization potential (4.98 eV), 17 its TFT performances can be easily degraded by oxidative doping in air. 8 Recently, Ackermann et al reported oligothiophenes end-capped with styryl and divinylbenzene end-capped with oligothiophenes, which showed high fieldeffect mobility with high stability. 18,19 Our group also reported small fused acenes containing divinylbenzene which showed not only good mobilities but also good oxidation stability.…”
Section: Introductionmentioning
confidence: 99%